Development of a New Teaching Model to Promote the Development of Second Graders' Metacognitive Monitoring - Ma Yuehuan; Ying Zhou (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2022)
This paper is an empirical one.